Thrombotic microangiopathic haemolytic anaemia and antiphospholipid antibodies. Issue 6 (12th May 2004) - Espinosa, G; Bucciarelli, S; Cervera, R; Lozano, M; Reverter, J-C; de la Red, G; Gil, V; Ingelmo, M; Font, J; Asherson, R A
Abstract : Objective: To analyse the clinical and laboratory features of patients with thrombotic microangiopathic haemolytic anaemia (TMHA) associated with antiphospholipid antibodies (aPL). Methods: A computer assisted (PubMed) search of the literature was performed to identify all cases of TMHA associated with aPL from 1983 to December 2002. Results: 46 patients (36 female) with a mean (SD) age at presentation of TMHA of 34 (15) years were reviewed. Twenty eight (61%) patients had primary antiphospholipid syndrome (APS). TMHA was the first clinical manifestation of APS in 26 (57%) patients. The clinical presentations were haemolytic-uraemic syndrome (26%), catastrophic APS (23%), acute renal failure (15%), malignant hypertension (13%), thrombotic thrombocytopenic purpura (13%), and HELLP (haemolysis, elevated liver enzymes, and low platelet count in association with eclampsia) syndrome (4%). Lupus anticoagulant was detected in 86% of the episodes of TMHA, and positive anticardiolipin antibodies titres in 89%. Steroids were the most common treatment (69% of episodes), followed by plasma exchange (PE) (62%), anticoagulant or antithrombotic agents (48%), immunosuppressive agents (29%), and immunoglobulins (12%). Recovery occurred in only 10/29 (34%) episodes treated with steroids, and in 19/27 (70%) episodes treated with PE. Death occurred in 10/46 (22%) patients. Conclusions: The results emphasise the need for systematic screening for aPL in all patients with clinical and laboratory features of TMHA. The existence of TMHA in association with an APS forces one to rule out the presence of the catastrophic variant of this syndrome. PE is indicated as a first line of treatment for all patients with TMHA associated with aPL.